Prevention and personal budgets in the provision of Social Care Public Services: Two potential areas in the achievement of efficiency. The United Kingdom’s experience - Pontones Rosa, Carolina (Cuadernos de Trabajo Social, 2013)
The United Kingdom has become one of the leading countries in the thrust of the New Public Management and Governance principles, promoting value for money and transparency in the provision of social care public services. In turn, the current social and economic scenery poses, more than ever, the need for European countries, particularly for Spain, to improve social services’ delivery in order to cover the increasing demand at a lower cost and maintaining the levels of satisfaction. Against such a complicated goal, the aim of this paper is to depict two of the main initiatives undertaken by Local Government in the United Kingdom, which are currently regarded as sources of efficiency. These techniques are referred to, on the one hand, the investment in prevention policies to develop short term interventions, mainly specialized and intensive home care attention – reablemet – and, on the other, the implementation of personal budgets within the Self-directed Support System, as a new trend both to enhance choice and control for the users and to raise their role in shaping their care packages.